Determinants of Pulmonary Tuberculosis Cure Rate in Sragen Regency - Muyassaroh, Zuhrotul (HIGEIA (Journal of Public Health Research and Development), 2023)
Abstract Based on the Health Profile data of Sragen Regency, the success rate of the Tuberculosis program in Sragen Regency from 2019 tends to fluctuate. In 2019 the success rate in Sragen Regency reached 71.1% in 2019, then increased to 94% in 2020, and then fell back to 83.7% in 2021. The tuberculosis success rate in 2021 is still not achieved the national target of 90%. The cure rate in Sragen Regency still tends to be low. Based on data from the Health Profile of Sragen Regency in 2021, the cure rate for tuberculosis is 49%. This study aims to determine the factors that affected the cure rate of pulmonary tuberculosis patients in Sragen Regency. This type of research was observational quantitative research with retrospective cohort method. The study was conducted in September 2022. The total sample in this study is 341 samples after exclusion data. Data analysis used survival analysis with Kaplan-Meier and log rank test. Occupation status (p=0,024), residence area (p=0,049) and TB history (p=0,017) have a relationship with the cure rate of pulmonary TB patients in Sragen Regency. Abstrak Berdasarkan Data Profil Kesehatan Kabupaten Sragen, angka keberhasilan pada program pengobatan TB dari 2019 cenderung fluktuatif. Pada tahun 2019, angka keberhasilan (success rate) di Kabupaten Sragen mencapai 71.1%, kemudian naik menjadi 94%, dan kembali turun di angka 83.7% di tahun 2021. Success rate di tahun 2021 masih belum mencapai target nasional yaitu 90%. Angka kesembuhan di Kabupaten Sragen cenderung masih rendah. Berdasarkan data Profil Kesehatan Kabupaten Sragen tahun 2021, angka kesembuhan TB di Kabupaten Sragen yaitu 49%. Penelitian ini bertujuan untuk mengetahui factor yang mempengaruhi laju kesembuhan TB paru di Kabupaten Sragen. Jenis penelitian yaitu penelitian kuantitatif observasional dengan metode kohort retrospektif. Penelitian ini dilaksanakan pada bulan September 2022. Total sampel yang digunakan pada penelitian ini yaitu 341 sampel setelah data dieksklusi. Analisis data dilakukan dengan analisis survival menggunakan Kaplan-Meier dan uji log-rank. Status pekerjaan (p=0,024), area tempat tinggal (p=0,049), dan riwayat TB (p=0,017) mempengaruhi laju kesembuhan pasien TB paru di Kabupaten Sragen.